Languages of Life and the Blending of Worlds: Radical Entanglement - Stuckrad, Kocku von (Journal for the study of religion, nature and culture, 2024)
Addressing the links between religion and experiences of nature requires language, and at the same time it moves beyond linguistic forms of communication. After a brief review of the linguistic paradigm in the study of religion, the question of linguistic understandings of nature is addressed from two perspectives. First, linguistic approaches attempt to include experiences of nature in our knowledge about the natural world and the human place within it; these perspectives usually extend linguistic knowledge to poetic expressions. Second, approaches that problematize the focus on linguistic communication altogether favor non-linguistic or semiotic interpretations of human communication with the more-than-human world. Making use of biosemiotics and other interdisciplinary research, an argument is made for radical entanglement and a scholarly strategy to coordinate the languages of life and to blend the different worlds and perspectives that we find on the planet.